2009
DOI: 10.1016/j.jnoncrysol.2009.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Relation between configurational entropy and relaxation dynamics of glass-forming systems under volume and temperature reduction

Abstract: The structural relaxation dynamics of two molecular glass forming systems have been analyzed by means of dielectric spectroscopy, under cooling and compression conditions. The relation of the dynamic slowing down with the reduction of the configurational entropy, S C , as predicted by Adam and Gibbs (AG), was also investigated. As S C is not directly accessible by experiments, it was estimated, following a common procedure in literature, from the excess entropy S exc of the supercooled liquid with respect to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The reliability of these investigations is demonstrated by comparing results obtained from two polymeric systems selected for their amorphous structure: polystyrene (PS), considered as a reference material because extensively studied by F-DSC, and poly(ethylene terephthalate)-glycol (PETg) which is much rarely studied by F-DSC techniques. In a second time, the temperature dependence of the cooling rate obtained by F-DSC and DSC combination has been compared to the temperature dependence of the relaxation times classically obtained from broadband dielectric spectroscopy, experiment considered as the reference concerning the fragility measurements [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of these investigations is demonstrated by comparing results obtained from two polymeric systems selected for their amorphous structure: polystyrene (PS), considered as a reference material because extensively studied by F-DSC, and poly(ethylene terephthalate)-glycol (PETg) which is much rarely studied by F-DSC techniques. In a second time, the temperature dependence of the cooling rate obtained by F-DSC and DSC combination has been compared to the temperature dependence of the relaxation times classically obtained from broadband dielectric spectroscopy, experiment considered as the reference concerning the fragility measurements [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent research 33 it was found that the ratio g P ͑T͒ / g T ͑P atm ͒ is approximately a constant temperature function and its value is usually slightly bigger than one. ͑18͒, i.e., the ratio g p / g T , needs to be found.…”
Section: -6mentioning
confidence: 99%